Radiographic Features of Knee Osteoarthritis: A Literature Review - Rosdiana Rosdiana; Febie Irsandy Syahruddin; Andi Dhedie Prasetia Sam; Shofiyah Latief; Fadil Mula Putra (Jurnal EduHealth, 2026)
Knee osteoarthritis is a degenerative joint disease that commonly causes chronic knee pain, limited mobility, and reduced quality of life in older adults. Conventional radiography (X-ray) remains the primary modality for initial evaluation due to its wide availability, cost-effectiveness, and ability to demonstrate characteristic structural changes such as joint space narrowing, osteophyte formation, subchondral sclerosis and cysts, and articular deformities. This literature review analyzed 20 national and international articles published between 2020 and 2025, retrieved from PubMed, ScienceDirect, Google Scholar, and Garuda using the PRISMA selection method. The findings indicate that appropriate examination techniques, particularly anteroposterior weight-bearing, lateral, and skyline projections, significantly influence the accuracy of radiological interpretation, while the Kellgren–Lawrence system remains the standard for grading disease severity. Radiography plays an essential role in early intervention planning, emergency department triage, and orthopedic referral, with additional modalities such as MRI and ultrasonography used to detect soft tissue abnormalities or early changes not yet visible on X-ray; moreover, emerging applications of deep learning and radiomics show promise in improving assessment consistency and predicting disease progression.